Multilingual and Multiword Phenomena in a lemon Old Occitan Medico-Botanical Lexicon - Bellandi, Andrea; Giovannetti, Emiliano; Weingart, Anja (My University, 2018)
This article illustrates the progresses made in representing a multilingual and multi-alphabetical Old Occitan medico-botanical lexicon in the context of the project Dictionnaire de Termes Médico-botaniques de l’Ancien Occitan (DiTMAO). The chosen lexical model of reference is lemon, which has been extended accordingly to some specific linguistic and lexical features of the lexicon. In particular, issues and solutions about the modeling of multilingual and multiword phenomena are discussed, as the way they are managed through LexO, a web editor developed in the context of the project.
Keywords: lemon model; RDF; historical lexicon; medico-botanical terminology; Old Occitan; Hebrew; Arabic; LexO web editor; 400